Management of Human Emotions and Stress in Facing Life's Competition Based on Psychological Aspects and Stoicism Philosophy to Achieve Happiness - Purwaningsih, Syukriyya Zuhrotul Endang (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Human life feels increasingly difficult every day because of the competition in life. Humans always feel dissatisfied with what they have achieved when they see and compare their own achievements with those of others. A person's standard of happiness is measured by his success in facing life's competition, resulting in reasonableness in managing emotions. As a result, a person will experience mental disorders such as anxiety, overthinking, and depression and even prolonged stress. This research aims to examine how the philosophy of stoicism can help humans face the competition of life by looking at a person's ability to achieve happiness. The research method is a literature study with a descriptive analytical approach. The analysis technique is carried out through literature studies selected based on research into various journals, books and other literature sources. This psychological problem will involve the philosophy of Stoicism which teaches emotional processing about how a person places the standard of happiness under his own control and keeps his mind calm without caring about bad things that will happen. Stoicism teaches not to focus on other people's standards or targets, but to focus on oneself.